Zachowania zdrowotne studentów pielęgniarstwa w zakresie profilaktyki chorób nowotworowych = The health behaviours of nursing students related to the prevention of neoplastic diseases - Dominika Gujska; Anastazja Gutek; Natalia Gajewska; Żaneta Gawron; Marcin Stanisław Rząca; Zdzisława Szadowska-Szlachetka (Kazimierz Wielki University, 2016)
Gujska Dominika, Gutek Anastazja, Gajewska Natalia, Gawron Żaneta, Rząca Marcin, Szadowska-Szlachetka Zdzisława. Zachowania zdrowotne studentów pielęgniarstwa w zakresie profilaktyki chorób nowotworowych = The health behaviours of nursing students related to the prevention of neoplastic diseases. Journal of Education, Health and Sport. 2016;6(6):107-120. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54714 http://ojs.ukw.edu.pl/index.php/johs/article/view/3546   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Zachowania zdrowotne studentów pielęgniarstwa w zakresie profilaktyki chorób nowotworowych The health behaviours of nursing students related to the prevention of neoplastic diseases   1Dominika Gujska, 1Anastazja Gutek, 1,2Natalia Gajewska, 1,3Żaneta Gawron, 4Marcin Rząca, 4Zdzisława Szadowska-Szlachetka 1Dominika Gujska, 1Anastazja Gutek, 1,2Natalia Gajewska, 1,3Zaneta Gawron, 4Marcin Rzaca, 4Zdzislawa Szadowska-Szlachetka   1Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Students scientific association, Chair of Oncology and Enviromental Health, Medical University of Lublin 2Oddział Hematologii, Onkologii i Transplantologii Dziecięcej, Uniwersytecki Szpital Dziecięcy w Lublinie University Children's Hospital in Lublin, Department: of Hematology , Oncology and Transplantation Children 3Oddział Otolaryngologii Dziecięcej, Foniatrii i Audiologii, Uniwersytecki Szpital Dziecięcy w Lublinie, University Children's Hospital in Lublin. Department of Pediatric Otolaryngology , Audiology and Phoniatrics 4Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Department of Oncology, Chair of Oncology and Enviromental Health, Medical University of Lublin   Słowa kluczowe: studenci pielęgniarstwa, świadomość zdrowotna, zachowania zdrowotne, choroba nowotworowa, profilaktyka nowotworów. Key words: nursing students, health awareness, health behaviours, neoplastic disease, prevention of neoplastic diseases.   Streszczenie Wstęp: Choroby nowotworowe stają się coraz bardziej powszechnym problemem na świecie. Dlatego ważne jest, żeby młodzi ludzie byli świadomi tego zagrożenia i wiedzieli jak postępować aby nie zachorować oraz znali metody wczesnego wykrywania nowotworów. Cel pracy: Poznanie wiedzy i zachowań zdrowotnych studentów pielęgniarstwa w zakresie profilaktyki nowotworów. Materiał i metody: Badania przeprowadzono wśród 105 studentów pielęgniarstwa Uniwersytetu Medycznego w Lublinie. Wśród respondentów było 7 mężczyzn i 98 kobiet. Narzędzie badawcze stanowił autorski kwestionariusz ankiety za pomocą którego zbadano poziom wiedzy i kwestionariusz standaryzowany Inwentarz Zachowań Zdrowotnych wg  Juczyńskiego. Wyniki badań poddano analizie statystycznej przy pomocy programu StatSoft Statistica 10.0 PL. Wyniki: Ogólny poziom wiedzy studentów na temat chorób nowotworowych był na wysokim poziomie. Najwięcej prawidłowych odpowiedzi studenci wskazywali w pytaniach dotyczących wiedzy na temat czynników ryzyka i objawów chorób nowotworowych, natomiast ich wiedza na temat profilaktyki była na poziomie przeciętnym. Studenci przejawiają zachowania prozdrowotne we wszystkich grupach zachowań wyodrębnionych przez Juczyńskiego w jego kwestionariuszu, najrzadziej w zakresie  praktyk zdrowotnych. Wnioski: • Studenci posiadają  wysoki poziom wiedzy dotyczący czynników ryzyka oraz objawów nowotworów, natomiast wymagają uzupełnienia treści związanych z profilaktyką wtórną nowotworów. • Studenci przejawiają zachowania  prozdrowotne. • Wysoki poziom wiedzy dotyczący  profilaktyki nowotworów nie zawsze towarzyszy praktykom zdrowotnym studentów.   Abstract Introduction: Neoplastic diseases are becoming a more and more common issue worldwide. Therefore, it is crucial for young people to be aware of the risks and know how to prevent neoplastic diseases and detect them at an early stage. Aim: The objective of the study was to gather information on the knowledge and health behaviours of nursing students related to the prevention of neoplastic diseases. Material and methods: The survey was carried out among 105 students of nursing from the Medical University of Lublin. The survey group consisted of 7 men and 98 women. The questionnaire prepared by the authors and the standardised Health Behaviour Inventory by Juczyński were used as research tools for identifying the level of the students' knowledge. The statistical analysis of the survey results was carried out with the use of the StatSoft Statistica 10.0 PL software. Results: The general level of the students' knowledge on neoplastic diseases was high.  The highest number of correct answers was provided for questions on the risk factors and symptoms of neoplastic diseases, while their knowledge on prophylactics was at a medium level. The students reported pro-health behaviours in all groups of behaviours identified in Juczyński's questionnaire, with the least favourable results referring to health practices. Conclusions: • The students demonstrated a  high level of awareness of the risk factors and symptoms of neoplastic diseases, while their knowledge on secondary prevention of neoplasms needs to be supplemented. • The students showed pro-health behaviours. • A high level of knowledge on neoplastic diseases prevention does not always correspond to the students' health practices.